Obesity and fracture risk - Gonnelli, Stefano (CIC Edizioni Internazionali, 2014)
Obesity and osteoporosis are two common diseases with an increasing prevalence and a high impact on morbidity and mortality. Obese women have always been considered protected against osteoporosis and osteoporotic fractures. However, several recent studies have challenged the widespread belief that obesity is protective against fracture and have suggested that obesity is a risk factor for certain fractures. Fat and bone are linked by many pathways, which ultimately serve the function of providing a skeleton appropriate to the mass of adipose tissue it is carrying. Leptin, adiponectin, adipocytic estrogens and insulin/amylin are involved in this connection. However, excessive body fat, and particularly abdominal fat, produces inflammatory cytokines which may stimulate bone resorption and reduce bone strength. This review aimed to examine the literature data on the relationships of BMI and fat mass with factures in adult and elderly subjects. Even though the more recent studies have shown conflicting results, there is growing evidence that obesity, and particularly severe obesity, may be related to an increased risk of fracture at different skeletal sites which is partially independent from BMD. Moreover, the relationship between obesity and fracture appears to be markedly influenced by ethnicity, gender and fat distribution. Even though the incidence and the pathogenesis of fracture in obese individuals has not yet been clearly defined, the growing evidence that obesity may be related to an increased risk of fracture has important public health implications and emphasizes the need to develop effective strategies to reduce fracture risk in obese subjects.